2010
DOI: 10.1021/ac1028853
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots with Phenylboronic Acid Tags for Specific Labeling of Sialic Acids on Living Cells

Abstract: Sialic acids with a nine-carbon backbone are commonly found at the terminal position of the glycans structures on cell membranes. The unique distribution and ubiquitous existence of sialic acid on the cell membrane make them important mediators in various biological and pathological processes. We report a new class of imaging probes based on semiconductor quantum dots with small molecular phenylboronic acid tags for highly specific and efficient labeling of sialic acid on living cells. Our results have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 46 publications
3
112
0
Order By: Relevance
“…Duan and colleagues employed carbodiimide chemistry in combination with a phenylboronic acid (PBA)-diol reaction to specifically label living cells with a QD-PBA conjugate. 203 They functionalized the hydrophobic QDs by an amphiphilic copolymer of maleic anhydride and octadecene (PMO) to obtain water-soluble QDs with carboxyl groups, which can react with 3-amino-phenylboronic acid (APBA) via an EDACcatalyzed reaction to form QD-PBA conjugates. The PBAdiol reaction allows for specific labeling of sialic acid by the QDs, and the bright QDs enable quantitative analysis of diffusion dynamics of sialic acids on the membrane.…”
Section: Covalent Conjugation Strategymentioning
confidence: 99%
“…Duan and colleagues employed carbodiimide chemistry in combination with a phenylboronic acid (PBA)-diol reaction to specifically label living cells with a QD-PBA conjugate. 203 They functionalized the hydrophobic QDs by an amphiphilic copolymer of maleic anhydride and octadecene (PMO) to obtain water-soluble QDs with carboxyl groups, which can react with 3-amino-phenylboronic acid (APBA) via an EDACcatalyzed reaction to form QD-PBA conjugates. The PBAdiol reaction allows for specific labeling of sialic acid by the QDs, and the bright QDs enable quantitative analysis of diffusion dynamics of sialic acids on the membrane.…”
Section: Covalent Conjugation Strategymentioning
confidence: 99%
“…Gac et al have successfully detected apoptotic cells by conjugating QDs with biotinylated Annexin V, which enables the functionalized QDs to bind to phosphatidylserine (PS) moieties present on the membrane of apoptotic cells but not on healthy or necrotic cells [36]. Liu et al reported the development of Gd-doped ZnO QDs with enhanced yellow fluorescence, and these QDs can be used as nanoprobes for quick cell detection with very low toxicity [37]. In 2007, Bagalkot et al reported a more complex QDsaptamer-(Apt-) doxorubicin (Dox) conjugate system [QDApt(Dox)] to endow QDs with the capability of targeting, imaging, therapy, and sensing the prostate cancer cells that express the prostate-specific membrane antigen (PSMA) protein [38].…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%
“…Previous research reported that phenyl-boronic acid (PBA) can form favorable bonds with sialic acid among common carbohydrates on the cell surface at the physiological pH of 7.4 (Otsuka et al, 2003). Recently, Liu et al, proposed the use of PBA-tagged quantum dots to label sialic acid on cell membranes for fluorescence imaging (Liu et al, 2010). Inspired by their work, we adopt DBA, a compound that consists of sialic acid capture moiety (phenyl-boronic) and alkyne functional group in our designed study (Fig.…”
Section: Introductionmentioning
confidence: 99%